Characterization of electrochemical transducers for biosensor applications - Arris, Farrah Aida; Benoudjit, Abdel Mohsen; Sanober, Fahmi; Wan Salim, Wan Wardatul Amani (Springer Nature, 2018)
Biosensors are devices that detect and report the presence or quantity of a particular analyte. Among the biosensor components, a physicochemical transducer measures physical and chemical changes from analyte-recognition interactions where products, by-products, intermediates, or physical changes are converted into a measurable signal. The character of the transducer determines the performance of a biosensor; hence the characterization of the transduction is crucial in the design of a biosensor. This chapter describes electrochemical characterization of the transducer layer of a biosensor via cyclic voltammetry.